Pengaruh Model Student Teams Achievement Divisions Terintegrasi Crossword Puzzle terhadap Motivasi dan Hasil Belajar Kognitif Siswa - Mirawati, Mirawati (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
Based on the results of initial observations at SMA Negeri 1 Praya Timur, Central Lombok Regency, it was found that students were still less motivated to be active in the learning process, such as lack of student readiness to start lessons, less attention to the teacher while teaching in class, less enthusiastic in learning, and a lack of curiosity when the teacher explains the subject matter. These things are because not all teachers apply appropriate and varied learning strategies, methods and models in learning activities, especially in biology lessons. Learning that takes place in the classroom is still teacher-centered, resulting in students becoming passive because they only tend to listen, pay attention, and take notes on the explanations given by the teacher. This has an impact on students' cognitive learning outcomes. The purpose of this study was to determine